For the first one:
Simplifying
ax + by = 12
Solving
ax + by = 12
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-1by' to each side of the equation.
ax + by + -1by = 12 + -1by
Combine like terms: by + -1by = 0
ax + 0 = 12 + -1by
ax = 12 + -1by
Divide each side by 'x'.
a = 12x-1 + -1bx-1y
Simplifying
a = 12x-1 + -1bx-1y
Reorder the terms:
a = -1bx-1y + 12x-1
For the second one:
Simplifying
2x + 8y = 60
Solving
2x + 8y = 60
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8y' to each side of the equation.
2x + 8y + -8y = 60 + -8y
Combine like terms: 8y + -8y = 0
2x + 0 = 60 + -8y
2x = 60 + -8y
Divide each side by '2'.
x = 30 + -4y
Simplifying
x = 30 + -4y
Hope I helped